Impact of Financial Risks on the Profitability of Systematically Important Banks in Nigeria. Issue 2 (December 2019) - Aluko, Olufemi Adewale; Kolapo, Funso Tajudeen; Adeyeye, Patrick Olufemi; Oladele, Patrick Olajide
This study examines the impact of financial risks in form of credit, interest rate and liquidity risk on the profitability of systematically important banks in Nigeria over the period from 2010 to 2016. The fixed effects regression model is estimated with Driscoll–Kraay standard errors in order to produce results that are robust to heteroscedaticity, autocorrelation, cross-sectional dependence and temporal dependence. After controlling for some bank-specific, industry-specific, macroeconomic and institutional factors, the empirical results show that credit and liquidity risks have a positive impact on bank profitability while interest rate does not have an impact. The results are robust to alternative measures of profitability.